Premium price for natural preservatives in wine: A discrete choice experiment - Lydia Chikumbi; Milan Scasny; Edwin Muchapondwa; Djiby Thiam (Charles University in Prague, Institute of Economic Studies (IES), 2020)
Recently, the South African wine industry launched the world's first "no sulphite added" wine made from indigenous Rooibos & Honey bush toasted wood chips. This wood chip contains antioxidants properties known to protect the wine from oxidation. On the other hand, SO2, as a preservative, is often perceived by wine consumers as causing headaches and migraine. Differentiated wines based on their SO2 content may be a profitable marketing avenue for the struggling industry. We interviewed more than 600 wine consumers to investigate perceptions on wine preservatives and to elicit willingness to pay for the innovative alternative based on Rooibos & Honey bush wood chips. Alongside the wine preservatives, we also examine consumers' preferences for organic wine attribute and wine quality measured by 100-points quality score, and the cost. Based on the results from the mixed logit model, we find that consumers are willing to pay additionally R56.48( exteuro3.53) per bottle of wine with natural Rooibos & Honey bush wood chips, while they are ready to pay R19.52( exteuro1.22) more for organic wine and R1.60( exteuro0.10) for each point on quality score. Consumer preferences are not statistically different between red and white wine but differ considerably across consumers, in particular, those who believe SO2 in wine cause headaches are willing to pay for replacing sulphur-based preservatives by a natural one at least three times more. Marketing implications are offered for the wine industry.
Keywords: O31; Q10; P46; 330; wine preservatives; willingness to pay; discrete choice experiment